2014
DOI: 10.1017/s1047951114001267
|View full text |Cite
|
Sign up to set email alerts
|

A case of neonatal myocardial infarction: left coronary artery thrombus resolution and normalisation of ventricular function by intracoronary low-dose tissue plasminogen activator

Abstract: Neonatal myocardial infarction is a rare clinical entity that is associated with high mortality. Reported treatment strategies include supportive care, extracorporeal membrane oxygenation, thrombolytics, and surgical thrombectomy. Herein we report a neonate who developed an acute myocardial infarction owing to a thrombus in the proximal left coronary artery. At 24 hours of life, he was treated with local (intracoronary) thrombolytic therapy at a lower dose than previously reported, as well as with systemic ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…10 Most recently, one case report described a neonate who developed an acute myocardial infarction from a thrombus at the bifurcation of the left anterior descending artery and left circumflex artery that was successfully treated with selective intracoronary tPA lysis and without ECMO support. 12 Our small case series highlights the utility and safety of tPA for treatment of neonatal coronary thrombi by specific use of the described protocol. Multiple studies and cases series have reported successful use of tPA and streptokinase in treatment of neonates with non -coronary artery thrombi.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…10 Most recently, one case report described a neonate who developed an acute myocardial infarction from a thrombus at the bifurcation of the left anterior descending artery and left circumflex artery that was successfully treated with selective intracoronary tPA lysis and without ECMO support. 12 Our small case series highlights the utility and safety of tPA for treatment of neonatal coronary thrombi by specific use of the described protocol. Multiple studies and cases series have reported successful use of tPA and streptokinase in treatment of neonates with non -coronary artery thrombi.…”
Section: Discussionmentioning
confidence: 84%
“…6,7,16,17 However, we could identify only three previous case reports of successful intracardiac tPA treatment of coronary artery thrombi. [10][11][12] The protocol described in our case series is our current standard approach. We believe that the protocol provides a safe and effective method for managing infants with mitral regurgitation and ventricular dysfunction resulting from coronary artery thrombi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some patients were on intravenous rTPA either before or after the intracoronary treatment. [10][11][12][13][14][15] Our patient was heparinized for ECMO, but child with HLHS. 6 The child was initially treated with 24 hr intravenous rTPA, which failed to achieve improvement.…”
Section: Discussionmentioning
confidence: 92%
“…However, in these reports, the doses were divided into 1–3 doses. In addition, some patients were on intravenous rTPA either before or after the intracoronary treatment . Our patient was heparinized for ECMO, but due to the risk of bleeding in light of open chest and being on ECMO, rTPA was only administered locally and not systemically.…”
Section: Discussionmentioning
confidence: 99%